In vivo Anticancer Activity on Ehrlich Ascites Carcinoma (EAC) Cells and in vitro Antimicrobial Activity of Psidium guajava Bark Extracts - Hossain, Md Jakir; Biswas, Shashwata; Shahriar, Mohammad; Islam, Sohidul; Ahsan, Chowdhury Rafiqul (Bangladesh Journal of Microbiology, 2019)
This study was performed to evaluate the in vivo anticancer activity against ehrlich ascites carcinoma (EAC) cells and in vitro antimicrobial activity of Psidium guajava bark extracts. By soxhlet apparatus, the P. guajava bark extracts were obtained using four solvents (n-hexane, petroleum benzene, chloroform, and methanol) according to their increasing solubility. In case of in vivo anticancer activity of the sample extracts, mice were seeded with approximately 1x105 ehrlich ascites carcinoma (EAC) cells. After seven days of consecutive treatment, the negative and positive control groups (n=8 each group) showed an average EAC cell count of 2.4x108 and 1.8x108 respectively, and the experimental groups showed the cell count of 2.2x 108, 2.1x108, 1.9x108, and 1.41x108 when mice received h-hexane, petroleum benzene, chloroform, and methanol extract respectively. Experimental group that received methanol extract showed percent increase of life span (% ILS) of 33.3 when compared with the negative control. However, treatment in a cyclic manner of the mice showed % ILS of 52.15 for experimental group when compared negative control. In antimicrobial activity experiment, an intermediate zone of sensitivity of the crude methanol extract was found against Escherichia coli, Shigella flexneri, and Staphylococcus aureus when compared with amoxicillin. All these results indicated the anticancer activity and antimicrobial activity of the methanol extract of P. guajava barks on different experimental models. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 79-81